PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA TERHADAP MODEL PEMBELAJARAN CONTEXTUAL TEACHING & LEARNING (CTL) BERBANTUAN VIDEO PEMBELAJARAN INTERAKTIF (VIPI) PADA SISWA KELAS III SD - Anggraeni, Deputri Rizky; Rini, Zulmi Roestika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to investigate the improvement of students' mathematical problem-solving abilities through the influence of the Contextual Teaching and Learning (CTL) learning model, incorporating interactive learning video media. This study employed a quantitative approach with a quasi-experimental design, specifically the Non-Equivalent Control Group Design type. The research subjects consisted of two classes: class III A, an experimental class that received CTL learning assisted by Interactive Learning Videos, and class III B, a control class that received CTL learning without the aid of Interactive Learning Videos. Data collection techniques were carried out through problem-solving ability tests, questionnaires, and observations. Data analysis employed prerequisite tests, including normality and homogeneity tests, as well as hypothesis testing using independent sample t-tests and regression analysis. The study's results showed significant differences and influences in the understanding of problem-solving abilities between students who participated in CTL learning assisted by Interactive Learning Videos and those who participated in CTL learning without media. CTL learning, assisted by Interactive Learning Videos, was able to increase student engagement, facilitate mathematical problem-solving abilities, and create a more meaningful and enjoyable learning environment. Thus, the use of the CTL learning model assisted by Interactive Learning Videos has a positive effect on the mathematical problem-solving abilities of third-grade elementary school students.